The use of the Dynamics+ module in LIRA-CAD 2022 in the calculation of large-span buildings or structures for seismic impacts - I. G. Ovchinnikov; N. S. Bystrov (Архитектура, строительство, транспорт)
The article discusses the main goals of dynamic calculation of buildings and structures. The authors present a method for calculating a large-span steel spatial structure for seismic impacts using the Dynamics+ module in LIRA-CAD 2022 software package. The paper analyses the sequence of loading formation in the calculation scheme. It considers the cases when the calculation of buildings and structures for seismic impact must be carried out using accelerograms, seismograms or velocigrams. As a result, the authors obtained a calculation model that allows analyzing the dynamic behavior of a large-span spatial structure in different periods. Subsequently, it will be relevant for studying the resistance of this structure to progressive collapse under seismic impact.